Assessment of the Nurse’s Role Regarding drug Administration of Cardiovascular Patients - reslan, Sabah (Latakia University Journal -Medical Sciences Series, 2018)
The administration of medication is often a chief responsibility of the nurse. The practice of administering medication involves providing the patient with a substance prescribed and intended for the diagnosis, treatment and or prevention. Nurses are generally trained and authorized to administer medication. The aim of the study was, to assess the nurse's role regarding cardiovascular drug administration. The number of samples is 50 nurses in Alasad and Tishreen hospitals . Data were collected through application of observational check list consist of two part, part one was demographic sheet and part two about nurse’s responsibility regarding medication administration which include (before, during, after drug administration). Data were analyzed through the application of descriptive statistical analysis such as (frequency, percentages and grand mean of scores). The study showed that nurses' practices were inadequate with low grand mean of score in most items regarding assessment of patients before, during and after drug administration. The recommendation was to Increase nursing staff awareness about cardio vascular drug administration through performs training on cardiac medication administration, follow up nurses' practice during drug administration and follow up the five rights of cardiac drug administration for safety patient. تقييم دور الكادر التمريضي حول إعطاء الأدوية للمرضى المصابين بأمراض القلب و الأوعية الدموية يعتبر إعطاء الأدوية المسؤولية الرئيسية للممرض/ة , حيث تشمل ممارسة إعطاء الأدوية تزويد المريض بالمادة الموصوفة والمعدة من اجل التشخيص أو العلاج, أو الوقاية. لذا يجب أن يدرب الكادر التمريضي ويفوض لإعطاء الأدوية. هدف الدراسة هو تقييم دور الكادر التمريضي حول إعطاء الأدوية للمرضى المصابين بأمراض القلب و الأوعية الدموية. أجريت الدراسة على عينة قوامها (50) مفردة غير احتمالية من الكوادر التمريضية في كل من مشفى الأسد الجامعي و مشفى تشرين الجامعي ,حيث جمعت البيانات من خلال استعمال قائمة الملاحظات المؤلفة من قسمين القسم الأول , صحيفة المعلومات الديموغرافية والقسم الثاني مسؤولية الكادر التمريضي المتعلق بإعطاء الأدوية والتي تتضمن( قبل, أثناء, بعد إعطاء الأدوية). أظهرت نتائج الدراسة بأن الممارسات التمريضية حول إعطاء الأدوية لمرضى القلب و الأوعية الدموية كانت غير مرضية. هذا بالإضافة إلى أن القليل من الكادر التمريضي كان يقيم المريض قبل و أثناء و بعد إعطاء الأدوية في كلا المستشفيين بنفس المستوى . تم تحليل البيانات باستخدام التحليل الإحصائي )المتوسط الإجمالي (. كانت التوصيات زيادة معرفة وممارسة الكوادر التمريضية من خلال فتح دورات تدريبية لهم حول كيفية إعطاء الأدوية للمرضى المصابين بأمراض القلب و الأوعية الدموية و أيضا متابعة الكادر التمريضي من قبل مشرقيين من أجل تنفيذ الصحاح الخمس عند إعطاء الأدوية للمرضى وذلك للحفاظ على سلامة المرضى.